2017
DOI: 10.1016/j.neuropharm.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic attenuation of chronic pain using mu opioid and cannabinoid receptor 2 agonists

Abstract: The misuse of prescription opiates is on the rise with combination therapies (e.g. acetaminophen or NSAIDs) resulting in severe liver and kidney damage. In recent years, cannabinoid receptors have been identified as potential modulators of pain and rewarding behaviors associated with cocaine, nicotine and ethanol in preclinical models. Yet, few studies have identified whether mu opioid agonists and CB2 agonists act synergistically to inhibit chronic pain while reducing unwanted side effects including reward li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 64 publications
9
55
0
Order By: Relevance
“…Coadministration of morphine with the CB 2 agonist JWH015 synergistically inhibited preclinical inflammatory, postoperative, and neuropathic pain in a doseand time-dependent manner (Grenald et al, 2017). The observed synergism may involve activation of CB 2 receptors on immune cells and subsequent inhibition of the inflammatory process coupled with morphine's well characterized ability to inhibit nociceptive signaling (Grenald et al, 2017). In keratinocytes in peripheral paw tissue, AM1241 stimulated the release of the endogenous opioid b-endorphin, which acted at local neuronal MORs to inhibit nociception through a naloxone-dependent mechanism (Ibrahim et al, 2005); however, naloxone sensitivity is not a class effect of CB 2 agonists and cannot account for AM1241 antinociception (Rahn et al, Fig.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Coadministration of morphine with the CB 2 agonist JWH015 synergistically inhibited preclinical inflammatory, postoperative, and neuropathic pain in a doseand time-dependent manner (Grenald et al, 2017). The observed synergism may involve activation of CB 2 receptors on immune cells and subsequent inhibition of the inflammatory process coupled with morphine's well characterized ability to inhibit nociceptive signaling (Grenald et al, 2017). In keratinocytes in peripheral paw tissue, AM1241 stimulated the release of the endogenous opioid b-endorphin, which acted at local neuronal MORs to inhibit nociception through a naloxone-dependent mechanism (Ibrahim et al, 2005); however, naloxone sensitivity is not a class effect of CB 2 agonists and cannot account for AM1241 antinociception (Rahn et al, Fig.…”
Section: Discussionmentioning
confidence: 98%
“…CB 2 activation is Role of CB 2 in Morphine Tolerance and Dependence correlated with increasing anti-inflammatory gene expression in the dorsal horn and reductions in mechanical and thermal hypersensitivities. Coadministration of morphine with the CB 2 agonist JWH015 synergistically inhibited preclinical inflammatory, postoperative, and neuropathic pain in a doseand time-dependent manner (Grenald et al, 2017). The observed synergism may involve activation of CB 2 receptors on immune cells and subsequent inhibition of the inflammatory process coupled with morphine's well characterized ability to inhibit nociceptive signaling (Grenald et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…These receptors are expressed on the microglia and modulate their action, and under pain conditions they are exposed on the cell surface. [35][36][37] Our data preliminarily suggest that phytochemicals as add-on therapy may represent an effective source of analgesics to be added to chemically synthesized drugs. As observed in this study, a combined therapeutic approach may result in decreased suffering and a general increase in QoL in elderly people.…”
Section: Resultsmentioning
confidence: 76%
“…These pain states include measures of acute analgesia, as well as neuropathic, inflammatory, and cancer pain modalities (Elikottil et al, 2009;Xiong et al 2011;Rock et al, 2019). Likewise, a large number of receptor systems have been implicated in mediating cannabinoid analgesia, including the cannabinoid receptors themselves (Mulpuri et al, 2018;Li et al 2019;Grenald et al, 2017), TRP channels (Muller et al, 2019), G protein-coupled receptors (RodrĂ­guez-Muñoz et al, 2018;Guerrero-Alba et al, 2019), and glycine receptors (Xiong et al, 2011(Xiong et al, , 2012. While many of these studies have focused on acute outcomes of only one or several drug administrations, long-term studies of cannabinoids in humans have shown mixed, and often subtle effects in treatment of pain (Vučković et al, 2018;Lötsch et al, 2018), suggesting that acute pain models may be inadequate when considering chronic pain.…”
Section: Introductionmentioning
confidence: 99%